Saliva: A potential diagnostic tool for oral cancer and oral diseases - A detailed review - P. Gopikrishna; A. Ramesh kumar; K. Rajkumar; R. Ashwini; Shruthi Venkatkumar (Oral Oncology Reports)
In this new era of genomic medicine, saliva chemistry plays a key role in the early detection, monitoring, and progression of oral and systemic diseases. The use of saliva to identify diseased individuals and track disease progression has attracted the attention of many researchers. It also offers a cost-effective approach to screen large populations. The main reason for using saliva as a diagnostic tool is that it contains serum components. The use of saliva as a diagnostic tool has recently become an uncontroversial part of clinical dentistry, primarily due to its non-invasive nature and the fact that it can be collected by people with minimal equipment and moderate training. This article provides a clear overview of the various diagnostic uses of saliva to determine the severity and progression of oral cancer and other oral diseases.